Perbandingan Kinerja Teknologi Failover berbasis Klaster (Heartbeat) dengan Teknologi Failover berbasis Jaringan (Keepalived) - Dian Pratama (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Today, data and information are very important. Data and information are generally processed and stored on servers. So that the data and information can always be accessed by users for 24 hours, a server with high availability is needed that can operate continuously and does not fail. The failover technique is one way to implement high-availability servers. The solution proposed by the researcher is the implementation of a high-availability server using Heartbeat and Keepalive software. This research implements two topologies, namely High Availability Web Server and High Availability Load Balancing. In the implementation of High Availability Web Server using a LAMP server, namely Linux Apache, Mysql and PHP for web content using WordPress. In the implementation of High Availability Load Balancing, Haproxy software is used to act as a load balancer. Tests are carried out in terms of functionality, downtime and failback. The test was carried out with 3 different scenarios and carried out 12 times of testing to find the average. From the results of functional testing, it is found that the implementation of the system has been running according to its function. . From the test results on the HA web server topology and HA load balancing topology, the lowest downtime values ​​in scenario 1 are 4 seconds and 4.05 seconds, in scenario 2 it is 0 seconds and 0 seconds, while in scenario 3 it is 0.88 seconds and 0 .78 seconds. In testing the failback topology of HA web server and HA load balancing, the lowest results were obtained in scenario 1 of 0.68 seconds and 0.48 seconds, in scenario 2 it was 0 seconds and 0 seconds while in scenario 3 it was 0.88 seconds and 0.53 second. Based on these results, the implementation of Keepalive or Heartbeat can be a solution for web server systems or load balancing that require high availability. Based on these results, the implementation of Keepalive or Heartbeat can be a solution for web server systems or load balancing that require high availability.